Hepatoid gland adenomas on the dorsal proximal part of a dog tail - Kaewsiri, Natnaree; Cha-umphol, Phinidda (Journal of Mahanakorn Veterinary Medicine, 2024)
A 4-year-old, 4.2 kg, Chihuahua, intact male dog visited the animal hospital due to the owner's concern over an over-lick behavior at the base of its tail that had continuously appeared for months. Physical examination at the base of the tail found change of skin color to purple-red bruise. The palpation showed a firm mass, 3*3*3 cm in size, located 5 cm from base of the tail. The histopathological examination results manifested as hepatoid gland adenoma, a rarely found tumor on the dorsal of base the tail. The veterinarian performed a successful surgical treatment with a good prognosis after surgery. The surgical wound appeared to be dry and healing smoothly. However, the dog should be monitored further because hepatoid gland adenoma has a 10–20 percent recurrence rate after surgery.